Verification and study of methodologies for determining goals for productive indicators - Silva, Fabiano Della Libera da; Spala, Saulo Tuayar (Brazilian Journal of Production Engineering, 2024)
This work reviews the literature on Key Performance Indicators (KPIs), addressing their concepts, importance, strategic value for organizations, and practical application as essential tools for business decision-making. It highlights the relevance of performance indicators, especially KPIs, defining them holistically and considering the specificities of different sectors. It emphasizes the importance of setting challenging but achievable goals and aligning these goals with the organization’s strategic objectives, ensuring their dissemination to all company levels. The Methodi Ordinatio multicriteria method was used, resulting in the selection of eleven relevant articles for systematic analysis, which formed the basis of the study. The analysis of the most significant works on indicators revealed the perception of the importance of KPIs for measuring and monitoring organizational processes. The work is structured as follows: introduction to the topic (section 1), theoretical foundation (section 2), methodological procedure (section 3), and results and discussions (section 4).